Fentanyl transdermal patch and preparation method thereof
By adding an annealing process during the preparation of fentanyl transdermal patches, 1-(2-phenethyl)-4-(N-phenylpropanamide)-piper in fentanyl transdermal patches in the prior art was solved by adding annealing process in the preparation of fentanyl transdermal patches. The problem of high content of hydrazine-N-oxide has achieved improvements in product quality and stability.
Patent Information
- Application Number
- CN202310959512.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-01
- Publication Date
- 2025-02-14
AI Technical Summary
The content of 1-(2-phenethyl)-4-(N-phenylpropanamide)-piperidine-N-oxide in the existing fentanyl transdermal patches is high, which affects product quality and lacks effective reduction of this Method for impurity content.
By adding an annealing process during the preparation of fentanyl transdermal patches, specifically annealing treatment for 2 to 5 hours under 70-100°C, the 1-(2-phenethyl)-4 in the finished product was significantly reduced. -(N-phenylpropanamide)-piperidine-N-oxide content.
The content of 1-(2-phenethyl)-4-(N-phenylpropanamide)-piperidine-N-oxide in fentanyl transdermal patch is less than 0.5%, which improves the quality and stability of the product. .
Smart Images

Figure BDA0004371236590000041 
Figure BDA0004371236590000101 
Figure BDA0004371236590000121
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of pharmaceutical preparations, and specifically, the present invention relates to a fentanyl transdermal patch and a preparation method thereof. More specifically, the present invention relates to a fentanyl transdermal patch and a preparation method thereof and a method for reducing impurities in the fentanyl transdermal patch. Background Art
[0002] Fentanyl is an opioid receptor agonist with an analgesic strength about 75-100 times that of morphine. It has been used for more than 60 years since it was first synthesized in 1960. Compared with morphine and pethidine, fentanyl has a rapid effect, a short duration of action, does not release histamine, has little effect on cardiovascular function, can inhibit the stress response during endotracheal intubation, and is particularly effective in treating intense and / or chronic pain, especially postoperative pain and pain in cancer patients. Fentanyl has a weaker depressive effect on respiration than morphine, but respiratory depression can still occur if injected intravenously too quickly.
[0003] In view of the fact that intravenous fentanyl can easily cause respiratory depression, fentanyl transdermal patches came into being. Fentanyl has a small molecular weight, good fat solubility, and low irritation, making it suitable for being made into transdermal patches. Fentanyl transdermal patches are also recommended for patients with gastrointestinal absorption disorders or dysphagia in the NCCN, EAPC, and ESMO cancer pain guidelines.
[0004] Existing literature records that fentanyl is unstable under oxidative conditions and can selectively generate a diastereoisomer N-oxide of fentanyl: 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide (Forced degradation of fentanyl: Identification and analysis of impurities and Degradants, Anuradha Garg*, Dennis W. Solas, etc.). Therefore, it is urgent to develop a fentanyl transdermal patch with low impurity content in 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the prior art to a certain extent. To this end, the present invention provides a fentanyl transdermal patch, wherein the content of 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide in the fentanyl transdermal patch is less than 0.5%, and the fentanyl transdermal patch has the advantages of low impurity content and high stability.
[0006] The present invention is accomplished based on the following findings of the inventors:
[0007] At present, my country has not yet formulated pharmacopoeia standards for the detection and limit of the content of 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide in fentanyl transdermal patches. The existing technologies of fentanyl transdermal patches have not paid attention to this impurity, and have not disclosed how to reduce the content of 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide.
[0008] The content of 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide in the product prepared by the preparation method of fentanyl transdermal patch discovered by the inventor of the present invention is relatively high, which may affect the product quality of fentanyl transdermal patch. However, the inventors studied the preparation method of fentanyl transdermal patch and unexpectedly found that when using the traditional preparation method, adding an annealing process can significantly reduce the content of 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide in the finished fentanyl transdermal patch.
[0009] Based on this, in one aspect of the present invention, a fentanyl transdermal patch is proposed. According to an embodiment of the present invention, the fentanyl transdermal patch comprises a backing layer, a drug-containing adhesive layer and a release layer; wherein the drug-containing adhesive layer comprises fentanyl or a pharmaceutically acceptable salt thereof; based on the total mass of the drug-containing adhesive layer, the mass percentage of 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide in the drug-containing adhesive layer is less than 0.5%. The content of 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide in the fentanyl transdermal patch of the present invention is less than 0.5%, and has the advantages of low impurity content and high stability.
[0010] According to an embodiment of the present invention, based on the total mass of the drug-containing gelatin layer, the mass percentage of the 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide is less than 0.4%.
[0011] According to an embodiment of the present invention, based on the total mass of the drug-containing gelatin layer, the mass percentage of the 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide is less than 0.3%.
[0012] According to an embodiment of the present invention, based on the total mass of the drug-containing gelatin layer, the mass percentage of the 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide is less than 0.2%.
[0013] In another aspect of the present invention, the present invention provides a method for preparing a fentanyl transdermal patch. According to an embodiment of the present invention, the method comprises: annealing a semi-finished fentanyl transdermal patch to obtain the fentanyl transdermal patch. The method of the present invention is simple to operate, and the content of 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide in the fentanyl transdermal patch prepared by the method is less than 0.5%, and the fentanyl transdermal patch has the advantages of low impurity content and high stability.
[0014] According to an embodiment of the present invention, the annealing treatment is performed at 70-100° C. for 2-5 hours.
[0015] According to an embodiment of the present invention, the annealing treatment is performed at 70-90° C. for 2-5 hours.
[0016] According to an embodiment of the present invention, the annealing treatment is performed at 75-85° C. for 2-4 hours.
[0017] According to an embodiment of the present invention, the annealing treatment is performed at 75-85° C. for 3-4 hours.
[0018] According to an embodiment of the present invention, the annealing treatment is performed at 80° C. for 2 to 4 hours.
[0019] According to an embodiment of the present invention, the annealing treatment is performed at 80° C. for 3 to 4 hours.
[0020] According to an embodiment of the present invention, the semi-finished fentanyl transdermal patch is obtained by the following steps: 1) coating a raw material mixture containing fentanyl or a pharmaceutically acceptable salt thereof on a release layer to obtain a drug-containing adhesive layer, wherein the release layer and the drug-containing adhesive layer are in contact; 2) covering the backing layer on the drug-containing adhesive layer to obtain the semi-finished fentanyl transdermal patch.
[0021] According to an embodiment of the present invention, in step 2), before covering the backing layer on the drug-containing adhesive layer, the drug-containing adhesive layer is dried in advance.
[0022] According to an embodiment of the present invention, in step 2), after the backing layer is covered on the drug-containing adhesive layer, a slitting process, a punching process and a packaging process are sequentially performed to obtain the semi-finished fentanyl transdermal patch.
[0023] In another aspect of the present invention, the present invention provides a method for reducing impurities in a fentanyl transdermal patch. According to an embodiment of the present invention, the method comprises: annealing a semi-finished fentanyl transdermal patch to obtain the fentanyl transdermal patch. The method according to the embodiment of the present invention can reduce the total impurity content in the fentanyl transdermal patch, especially can reduce the content of 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide (the content is less than 0.5%), and the fentanyl transdermal patch has the advantages of low impurity content and high stability.
[0024] According to an embodiment of the present invention, the impurity includes 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide.
[0025] According to an embodiment of the present invention, the annealing treatment is performed at 70-100° C. for 2-5 hours.
[0026] According to an embodiment of the present invention, the annealing treatment is performed at 70-90° C. for 2-5 hours.
[0027] According to an embodiment of the present invention, the annealing treatment is performed at 75-85° C. for 2-4 hours.
[0028] According to an embodiment of the present invention, the annealing treatment is performed at 75-85° C. for 3-4 hours.
[0029] According to an embodiment of the present invention, the annealing treatment is performed at 80° C. for 2 to 4 hours.
[0030] According to an embodiment of the present invention, the annealing treatment is performed at 80° C. for 3 to 4 hours.
[0031] According to an embodiment of the present invention, the semi-finished fentanyl transdermal patch is obtained by the following steps: 1) coating a raw material mixture containing fentanyl or a pharmaceutically acceptable salt thereof on a release layer to obtain a drug-containing adhesive layer, wherein the release layer and the drug-containing adhesive layer are in contact; 2) covering the backing layer on the drug-containing adhesive layer to obtain the semi-finished fentanyl transdermal patch.
[0032] According to an embodiment of the present invention, in step 2), before covering the backing layer on the drug-containing adhesive layer, the drug-containing adhesive layer is dried in advance.
[0033] According to an embodiment of the present invention, in step 2), after the backing layer is covered on the drug-containing adhesive layer, a slitting process, a punching process and a packaging process are sequentially performed to obtain the semi-finished fentanyl transdermal patch.
[0034] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION
[0035] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0036] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0037] Detailed description of the invention
[0038] Definitions and general terms
[0039] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0040] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.
[0041] As used herein, the terms "optionally", "optional" or "optionally" generally mean that the subsequently described event or circumstance may but need not occur, and that the description includes instances where the event or circumstance occurs and instances where it does not.
[0042] In this article, the term "pharmaceutically acceptable" means that the substance or composition must be chemically and / or toxicologically compatible with the other ingredients of the formulation and / or the mammals treated therewith. Preferably, the "pharmaceutically acceptable" of the present invention refers to those approved by federal regulatory agencies or national governments or listed in the U.S. Pharmacopoeia or other generally recognized pharmacopeias for use in animals, particularly humans.
[0043] As used herein, the term "pharmaceutically acceptable salts" refers to organic and inorganic salts of the compounds of the present invention. Pharmaceutically acceptable salts are well known in the art, as described in SM Berge et al., describe pharmaceutically acceptable salts in detail in J. Pharmaceutical Sciences, 1977, 66: 1-19.
[0044] In this article, the term "1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide" is the diastereoisomer N-oxide selectively generated by fentanyl under oxygen-containing conditions, with a CAS number of 85893-37-4 and a specific structure as follows:
[0045]
[0046] In this article, the term "%" means the mass percentage "wt%", which is interpreted as the content of a substance, or the proportion of a substance in a mixture. Specifically, in the present invention, the content of 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide is the proportion of 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide in the drug-containing gelatin layer.
[0047] In this article, the term "annealing" refers to heating a substance to a certain temperature, maintaining it for a certain period of time, and then cooling it to a suitable temperature. Specifically, in the present invention, annealing refers to placing the prepared fentanyl transdermal patch in an oven, maintaining it at a certain temperature for a certain period of time, and then naturally cooling it to room temperature after taking it out.
[0048] Detailed description of the fentanyl transdermal patch and its preparation method and method for reducing impurities in the fentanyl transdermal patch of the present invention
[0049] The present invention provides a fentanyl transdermal patch and a preparation method thereof and a method for reducing impurities in the fentanyl transdermal patch, which will be described in detail below.
[0050] Fentanyl transdermal patch
[0051] In the first aspect of the present invention, the present invention proposes a fentanyl transdermal patch. According to an embodiment of the present invention, the fentanyl transdermal patch includes a backing layer, a drug-containing adhesive layer and a release layer; wherein the drug-containing adhesive layer includes fentanyl or a pharmaceutically acceptable salt thereof; based on the total mass of the drug-containing adhesive layer, the mass percentage of 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide in the drug-containing adhesive layer is less than 0.5%. The content of 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide in the fentanyl transdermal patch of the present invention is less than 0.5%, and the related substances of the fentanyl transdermal patch of the present invention meet the quality standards, have the advantages of low impurity content and high stability, etc., and can be used as a coping strategy for the failure of end-of-dose analgesia of commercially available patches, or as an option for other chronic pain.
[0052] In this document, unless otherwise specified, “release layer” and “release film” are synonymous.
[0053] In some embodiments of the present invention, based on the total mass of the drug-containing gelatin layer, the mass percentage of the 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide is less than 0.4%.
[0054] In some embodiments of the present invention, based on the total mass of the drug-containing gelatin layer, the mass percentage of the 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide is less than 0.3%.
[0055] In some embodiments of the present invention, based on the total mass of the drug-containing gelatin layer, the mass percentage of the 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide is less than 0.2%.
[0056] In some embodiments of the present invention, the fentanyl transdermal patch is mainly composed of a backing layer, a release layer and a drug-containing adhesive layer.
[0057] In some embodiments of the present invention, the drug-containing gel layer may further include a pharmaceutically acceptable excipient or carrier.
[0058] As used herein, the term "pharmaceutically acceptable excipient or carrier" includes any solvent, cross-linking agent, adhesive, percutaneous absorption enhancer, solubilizer, plasticizer, antioxidant, crystallization inhibitor, stabilizer, skin irritation reducer, pH stabilizer, surfactant, preservative (e.g., antibacterial agent, antifungal agent), isotonic agent, salt, colorant, etc., or a combination thereof, and these carriers or excipients are all known to those skilled in the art (as described in Remington's Pharmaceutical Sciences, 18th Ed. Mack Printing Company, 1990, pp. 1289-1329).
[0059] In some embodiments of the present invention, the pharmaceutically acceptable excipient or carrier includes a binder and / or a cross-linking agent.
[0060] In this article, as for the selection of adhesives, as long as they are pharmaceutically acceptable and can achieve an adhesive effect, the specific type is not limited and all are within the protection scope of the present invention.
[0061] In some embodiments of the present invention, the adhesive may be a polyacrylate (acrylic polymer), which may include a copolymer or terpolymer containing at least two or more exemplary components, wherein the components are selected from acrylic acid, alkyl acrylate, methacrylate, a copolymerizable secondary monomer or a monomer having a functional group, for example, it may be selected from Henkel's DURO-TAK series pressure-sensitive adhesives; it may also be a natural rubber-based compound or a synthetic rubber-based compound in a rubber-based adhesive, exemplarily selected from one or more of the group consisting of polyisobutylene, polyisoprene, polybutadiene, and polybutene; it may also be a thermoplastic elastomer pressure-sensitive adhesive, exemplarily selected from one or more of styrene-isoprene-styrene block copolymer (SIS), styrene-butadiene-styrene block copolymer (SBS) or styrene-ethylene-butylene-styrene block copolymer (SEBS).
[0062] In this article, "crosslinking agent" refers to a substance that can affect the load-bearing properties of the adhesive and improve the cohesion and / or adhesion of the adhesive. Regarding the selection of the crosslinking agent, as long as it can improve the cohesion and / or adhesion of the adhesive, the specific type is not limited and all are within the scope of protection of the present invention.
[0063] In some embodiments of the present invention, the crosslinking agent includes but is not limited to an inorganic crosslinking agent selected from metals or metal compounds, or an organic crosslinking agent selected from thermosetting resins such as amino resins, phenolic resins, epoxy resins, alkyd resins, unsaturated polyesters, isocyanate compounds, and blocked isocyanate compounds.
[0064] Exemplarily, the crosslinking agent is an inorganic crosslinking agent, such as polybutyl titanate.
[0065] In some embodiments of the present invention, the pharmaceutically acceptable excipient or carrier further comprises a percutaneous absorption enhancer.
[0066] In this article, regarding the selection of percutaneous absorption enhancers, as long as they are pharmaceutically acceptable and can promote skin absorption, the specific type is not limited and all are within the scope of protection of the present invention.
[0067] In some optional embodiments of the present invention, the percutaneous absorption enhancer is one, two or more compounds that have been confirmed to have a percutaneous absorption enhancing effect on the drug. For example, fatty acids, fatty alcohols, fatty acid esters, alkyl ethers, aromatic organic acids, aromatic alcohols, aromatic organic acid esters, and aryl ethers having 6 to 20 carbon atoms can be listed; N-ketone (Azone) or its derivatives, lactic acid esters, acetate esters, monoterpene compounds, sesquiterpene compounds, fatty acid glycerides, fatty acid sorbitan esters, polysorbates, polyethylene glycol fatty acid esters, polyoxyethylene solidified castor oils, sucrose fatty acid esters, etc. can also be listed.
[0068] In some embodiments of the present invention, the pharmaceutically acceptable excipient or carrier further comprises at least one of a solubilizer, a plasticizer, an antioxidant, a crystallization inhibitor, a stabilizer, a skin irritation reducing agent, and a pH stabilizer.
[0069] In some embodiments of the present invention, the material of the backing layer can be cloth, non-woven fabric, polyurethane, polyester, polyvinyl acetate, polyvinylidene chloride, polyethylene, polyethylene terephthalate, polybutylene terephthalate, paper, aluminum sheet, etc. or a composite material thereof.
[0070] Exemplarily, the backing layer is one of 3M's scotchpak 9723, scotchpak 9720, scotchpak9754, scotchpak 9738, scotchpak 9718, scotchpak 9733, CoTran 9722, scotchpak 1109 or Japan Vilene Co., Ltd.'s EW series of medical backing nonwoven fabrics; in some other embodiments of the present invention, the backing layer is scotchpak 9723.
[0071] Herein, the release layer is selected to be compatible with the viscosity of the pharmaceutical composition so as to achieve a light and stable release force when peeled off. The specific type is not limited and is within the scope of protection of the present invention.
[0072] In some optional embodiments of the present invention, the material of the release layer can be PET (polyethylene terephthalate), PE (polyethylene), OPP (o-phenylphenol), and at least one of any of the above materials that have been plasma treated, coated or siliconized.
[0073] Method for preparing fentanyl transdermal patch and method for reducing impurities in fentanyl transdermal patch
[0074] In the second aspect of the present invention, the present invention proposes a method for preparing a fentanyl transdermal patch. According to an embodiment of the present invention, the method comprises: annealing a semi-finished fentanyl transdermal patch to obtain the fentanyl transdermal patch. The method of the present invention is simple to operate, and the content of 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide in the fentanyl transdermal patch prepared by the method is less than 0.5%, and the related substances of the prepared fentanyl transdermal patch meet the quality standards, and it has the advantages of low impurity content and high stability, etc., which can be used as a coping strategy for the failure of end-of-dose analgesia of commercially available patches, or as an option for other chronic pain.
[0075] In the third aspect of the present invention, the present invention proposes a method for reducing impurities in a fentanyl transdermal patch. According to an embodiment of the present invention, the method comprises: annealing a semi-finished fentanyl transdermal patch to obtain the fentanyl transdermal patch. The method according to the embodiment of the present invention can reduce the total impurity content in the fentanyl transdermal patch, especially can reduce the content of 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide (content less than 0.5%), and the related substances of the obtained fentanyl transdermal patch meet the quality standards, and it has the advantages of low impurity content and high stability, etc., which can be used as a coping strategy for the failure of end-of-dose analgesia of commercially available patches, or as an option for other chronic pain.
[0076] In some embodiments of the present invention, the impurity comprises 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide.
[0077] In some embodiments of the present invention, the methods described in the second and third aspects above may further include at least one of the following technical features:
[0078] In some embodiments of the present invention, the annealing treatment is performed at 70-100° C. for 2-5 hours.
[0079] Exemplarily, the annealing temperature is 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C. , 100℃ or any two of them as the range value between endpoint values, for example, 70℃~95℃, 70℃~90℃, 70℃~85℃, 70℃~80℃, 75℃~100℃, 75℃~95℃, 75℃~90℃, 75℃~85℃, 75℃~80℃, 80℃~100℃, 80℃~95℃, 80℃~90℃, 80℃~85℃.
[0080] Exemplarily, the annealing time is 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h or a range value between any two of them as endpoint values, for example, 2h~4.5h, 2h~4h, 2h~3.5h, 2h~3h, 2h~2.5h, 2.5h~5h, 2.5h~4.5h, 2.5h~4h, 2.5h~3.5h, 2.5h~3h, 3h~5h, 3h~4.5h, 3h~4h, 3h~3.5h.
[0081] In some embodiments of the present invention, the annealing treatment is performed at 70-90° C. for 2-5 hours.
[0082] In some embodiments of the present invention, the annealing treatment is performed at 75-85° C. for 2-4 hours.
[0083] In some embodiments of the present invention, the annealing treatment is performed at 75-85° C. for 3-4 hours.
[0084] In some embodiments of the present invention, the annealing treatment is performed at 80° C. for 2 to 4 hours.
[0085] In some embodiments of the present invention, the annealing treatment is performed at 80° C. for 3 to 4 hours.
[0086] In some embodiments of the present invention, the fentanyl transdermal patch semi-finished product is obtained by the following steps: 1) coating a raw material mixture containing fentanyl or a pharmaceutically acceptable salt thereof on a release layer to obtain a drug-containing adhesive layer, wherein the release layer and the drug-containing adhesive layer are in contact; 2) covering the backing layer on the drug-containing adhesive layer to obtain the fentanyl transdermal patch semi-finished product.
[0087] In some optional embodiments of the present invention, the raw material mixture contains fentanyl or a pharmaceutically acceptable salt thereof, and may further include a pharmaceutically acceptable excipient or carrier. The selection of pharmaceutically acceptable excipients or carriers is specifically referred to the fentanyl transdermal patch described in the first aspect of the present invention.
[0088] In some embodiments of the present invention, the raw material mixture is obtained by mixing fentanyl or a pharmaceutically acceptable salt thereof with a pharmaceutically acceptable excipient or carrier.
[0089] In some embodiments of the present invention, the mixing treatment comprises at least two mixing treatments, the first mixing treatment is to mix the solution that does not contain fentanyl or its pharmaceutically acceptable salt in the drug-containing adhesive layer (for example, a cross-linking agent and an adhesive), the stirring speed during mixing is 45-55rpm, and the stirring time is not less than 4h, and the second mixing treatment is to mix the solution containing fentanyl or its pharmaceutically acceptable salt in the drug-containing adhesive layer, the stirring speed during mixing is 45-55rpm, and the stirring time is not less than 2h.
[0090] In some embodiments of the present invention, a stock solution is prepared in advance before the mixing process. In some embodiments of the present invention, the stock solution includes a cross-linker stock solution, the solvent of which is a mixture of n-heptane and anhydrous ethanol; and a fentanyl stock solution, the solvent of which is anhydrous ethanol.
[0091] In some embodiments of the present invention, after the mixing process and before the coating, a rehydration and degassing process is performed. In some optional embodiments of the present invention, the rehydration means that if the net weight ratio of the mixture before and after the mixing process exceeds 2.0%, the solvent in the step of preparing the stock solution is added to make it reach the weight before mixing. In some embodiments of the present invention, the preparation method of the fentanyl transdermal patch is not subjected to a rehydration process, and in other embodiments of the present invention, the preparation method of the fentanyl transdermal patch is subjected to a rehydration process.
[0092] In some embodiments of the present invention, the coating speed is 0.3-0.5 m / min; the coating knife distance is 80-150 μm; and the coating width is 200-250 mm.
[0093] In some embodiments of the present invention, the coating speed is 0.4 (± 0.1) m / min; the coating knife distance is 110 (± 30) μm; and the coating width is 220 (± 10) mm.
[0094] In some embodiments of the present invention, in step 2), before covering the backing layer on the drug-containing adhesive layer, the drug-containing adhesive layer is dried in advance.
[0095] In some embodiments of the present invention, the drying temperature is 70°C-90°C, for example, 70°C, 75°C, 80°C, 85°C, 90°C or a range between any two of them as endpoint values, for example, 70°C-90°C, 70°C-85°C, 70°C-80°C, 70°C-75°C, 75°C-90°C, 75°C-85°C, 75°C-80°C, 80°C-90°C, 80°C-85°C.
[0096] In some embodiments of the present invention, a lamination process is performed in advance after the drying process and before the slitting process. In some optional embodiments of the present invention, the lamination process refers to laminating the drug-containing adhesive layer after the drying process onto the backing layer. In some embodiments of the present invention, the three process steps of coating, drying and lamination are all completed on a coating machine.
[0097] In some embodiments of the present invention, in step 2), after the backing layer is covered on the drug-containing adhesive layer, a slitting process, a punching process and a packaging process are sequentially performed to obtain the semi-finished fentanyl transdermal patch.
[0098] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0099] Example 1: Preparation method of fentanyl transdermal patch
[0100] The preparation method of fentanyl transdermal patch comprises the following steps:
[0101] Dividing materials: Divide the materials according to the prescribed dosage and place 25.1165 g of DURO-TAK 387-2510 acrylic pressure-sensitive adhesive directly into a 50 mL scientific vial.
[0102] Preparation of stock solution: Add anhydrous ethanol to a container containing 1.1600 g of fentanyl, mix until fentanyl is completely dissolved, and mark it as "fentanyl stock solution"; pour n-heptane into a container containing 0.0565 g of polybutyl titanate, stir manually for 3 minutes, add anhydrous ethanol, stir manually for 5 minutes, and mark it as "3% polybutyl titanate solution" (ethanol: n-heptane = 40:60).
[0103] mix: Add 3% polybutyl titanate solution to a 50mL scientific vial containing DURO-TAK 387-2510 acrylic pressure-sensitive adhesive, rinse the container with anhydrous ethanol twice, add all the solution to the scientific vial, set the stirring speed to 50rpm, and stir in a closed state for 4 hours until the mixture is evenly mixed; after the first stage of mixing is completed, add the fentanyl stock solution to a 50mL scientific vial, rinse the container with anhydrous ethanol three times, add all the solution to the scientific vial, set the stirring speed to 50rpm, and stir in a closed state for 2 hours until the mixture is evenly mixed.
[0104] Degassing:After the mixing was completed, the mixture was degassed with a negative pressure of -0.3 Mpa for 15 min, and stirring was continued at 50 rpm during the degassing period.
[0105] Coating, drying, laminating: All three process steps were completed on the coating machine. The key process parameters were set and adjusted according to the parameters in Table 1. At the same time, the coating thickness was monitored online so that it could be adjusted to the target range in time. The release film was PET 4400B release film. After drying, the backing position was adjusted to ensure that no obvious bubbles were generated during the lamination process. The backing layer was Scothpak 9723 backing film.
[0106] Table 1: Coating, drying and laminating process parameters
[0107]
[0108] Slitting, punching and packaging: The prepared fentanyl transdermal patch composite material was cut into sub-rolls with a width of 50 mm. After the cutting was completed, the sub-rolls were transferred to a punching and packaging machine for punching and packaging. The punching speed was 150 rpm. The heat sealing temperature during packaging was 160°C for the upper plate and 120°C for the lower plate to obtain the target fentanyl transdermal patch.
[0109] annealing: Half of the packaged fentanyl transdermal patches (which may also be referred to as semi-finished fentanyl transdermal patches before annealing) were placed in an oven at 70° C. for annealing for 2 h, and the other half were not annealed.
[0110] Example 2: Preparation method of fentanyl transdermal patch
[0111] The dosage of the fentanyl transdermal patch is the same as that of Example 1, but the preparation method has the following differences:
[0112] mix: The mixing procedure for the first stage is to set the stirring speed to 45 rpm and stir in a closed state for 5 hours; the mixing procedure for the second stage is to set the stirring speed to 50 rpm and stir in a closed state for 2.5 hours.
[0113] Degassing: The degassing pressure was a negative pressure of -0.2 MPa, the degassing time was 20 min, and the stirring speed during the degassing period was 55 rpm.
[0114] Coating, drying, laminating: The drying temperatures are: Zone 1: 75°C, Zone 2: 80°C, Zone 3: 85°C.
[0115] Slitting, punching and packaging: The punching speed was 200 rpm, and the heat sealing temperature during packaging was 170°C for the upper plate and 140°C for the lower plate.
[0116] annealing:Half of the packaged fentanyl transdermal patches were placed in an oven at 70°C for annealing for 4 hours, and the other half were not annealed.
[0117] Example 3: Preparation method of fentanyl transdermal patch
[0118] The dosage of the fentanyl transdermal patch is the same as that of Example 1, but the preparation method has the following differences:
[0119] mix: The mixing procedure for the first stage is to set the stirring speed to 55 rpm and stir in a closed state for 4 hours; the mixing procedure for the second stage is to set the stirring speed to 45 rpm and stir in a closed state for 3 hours.
[0120] Degassing: The degassing pressure was a negative pressure of -0.4 MPa, the degassing time was 15 min, and the stirring speed during the degassing period was 45 rpm.
[0121] Coating, drying, laminating: The drying temperatures are: zone 1: 80°C, zone 2: 85°C, zone 3: 90°C.
[0122] Slitting, punching and packaging: The punching speed was 100 rpm, and the heat sealing temperature during packaging was 150°C for the upper plate and 110°C for the lower plate.
[0123] annealing: Half of the packaged fentanyl transdermal patches were placed in an oven at 80°C for annealing for 2 hours, and the other half were not annealed.
[0124] Example 4: Preparation method of fentanyl transdermal patch
[0125] The dosage of the fentanyl transdermal patch is the same as that of Example 1, but the preparation method has the following differences:
[0126] mix: The mixing procedure for the first stage is to set the stirring speed to 45 rpm and stir in a closed state for 5 hours; the mixing procedure for the second stage is to set the stirring speed to 45 rpm and stir in a closed state for 3 hours.
[0127] Degassing: The degassing pressure was a negative pressure of -0.3 Mpa, the degassing time was 15 min, and the stirring speed during the degassing period was 50 rpm.
[0128] Coating, drying, laminating: The drying temperatures are: Zone 1: 75°C, Zone 2: 80°C, Zone 3: 85°C.
[0129] Slitting, punching and packaging: The punching speed was 150 rpm, and the heat sealing temperature during packaging was 160°C for the upper plate and 120°C for the lower plate.
[0130] annealing:Half of the packaged fentanyl transdermal patches were placed in an oven at 80°C for annealing for 4 hours, and the other half were not annealed.
[0131] Experimental Example 1: Effect of Annealing Process on Impurity Content of Fentanyl Transdermal Patch
[0132] The contents of 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide, the largest unknown single impurity and the total impurities in the fentanyl transdermal patches prepared in Examples 1-4 were determined by high performance liquid chromatography. The results are shown in Table 2.
[0133] It can be seen from the results in Table 2 that in the preparation process of the fentanyl transdermal patch, when the annealing step was not performed, the contents of 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide, the largest unknown single impurity and the total impurities in Examples 1 to 4 were almost the same. Therefore, it can be further explained that the steps of mixing, degassing, coating, drying, etc. have no effect on the content of related impurities in the finished fentanyl transdermal patch.
[0134] In Examples 1 to 4, when half of the packaged fentanyl transdermal patches were annealed and the other half were not annealed, the annealing treatment could effectively reduce the content of 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide in the fentanyl transdermal patches (all less than 0.5%), meeting the limit requirements, and the annealing process had no effect on the changes in the content of the maximum unknown single impurity and other impurities.
[0135] Table 2: Effect of annealing process on impurity content of fentanyl transdermal patch
[0136]
[0137]
[0138] Test Example 2: Stability Study of Fentanyl Transdermal Patch
[0139] The fentanyl transdermal patch subjected to annealing treatment in Example 3 of the present invention was taken to investigate the changes in the content of related substances in the long-term test, accelerated test, high temperature test, high humidity test, and light test of the transdermal patch. The specific investigation factors are shown in Table 3. The test results of the changes in the content of related substances of the fentanyl transdermal patch in the long-term test, accelerated test, high temperature test, high humidity test, and light test are shown in Tables 4 to 6, respectively.
[0140] From the test results of long-term, accelerated, high temperature, high humidity and light tests in Tables 4 to 6, it can be seen that the fentanyl transdermal patch prepared by the present invention meets the stability requirements and has good stability.
[0141] Table 3: Stability evaluation factors
[0142] Consideration factors Long-term trials 25℃±2℃, 60%RH±5%RH, 24 months Accelerated testing 40℃±2℃, 75%RH±5%RH, 6 months High temperature test 60℃, 30 days High humidity test 92.5% RH, 30 days Light test 4500Lx±500Lx, 30 days
[0143] Table 4: Results of long-term trial of fentanyl transdermal patch
[0144]
[0145] Table 5: Results of the accelerated test of fentanyl transdermal patch
[0146]
[0147]
[0148] Table 6: Results of the high temperature, high humidity and light test of fentanyl transdermal patch
[0149]
[0150] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0151] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A fentanyl transdermal patch, characterized in that: It includes a backing layer, a drug-containing adhesive layer and a release layer; Wherein, the drug-containing adhesive layer includes fentanyl or a pharmaceutically acceptable salt thereof; Based on the total mass of the drug-containing adhesive layer, the mass percentage of 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide in the drug-containing adhesive layer is less than 0.5%.
2. The fentanyl transdermal patch according to claim 1, characterized in that: Based on the total mass of the drug-containing gelatin layer, the mass percentage of the 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide is less than 0.4%.
3. The fentanyl transdermal patch according to claim 1 or 2, characterized in that: Based on the total mass of the drug-containing gelatin layer, the mass percentage of the 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide is less than 0.3%, preferably less than 0.2%.
4. A method for preparing a fentanyl transdermal patch, characterized in that: include: The semi-finished fentanyl transdermal patch is subjected to annealing treatment to obtain the fentanyl transdermal patch.
5. The method according to claim 4, characterized in that The annealing treatment is carried out at 70-100° C. for 2-5 hours; Optionally, the annealing treatment is performed at 70 to 90° C. for 2 to 5 hours; Optionally, the annealing treatment is performed at 75 to 85° C. for 2 to 4 hours; Optionally, the annealing treatment is performed at 75 to 85° C. for 3 to 4 hours; Optionally, the annealing treatment is performed at 80° C. for 2 to 4 hours; Optionally, the annealing treatment is performed at 80° C. for 3 to 4 hours.
6. The method according to claim 4 or 5, characterized in that: The semi-finished fentanyl transdermal patch is obtained by the following steps: 1) coating a raw material mixture containing fentanyl or a pharmaceutically acceptable salt thereof on a release layer to obtain a drug-containing adhesive layer, wherein the release layer and the drug-containing adhesive layer are in contact; 2) covering the drug-containing adhesive layer with a backing layer to obtain the semi-finished fentanyl transdermal patch; Optionally, in step 2), before covering the backing layer on the drug-containing adhesive layer, the drug-containing adhesive layer is dried in advance; Optionally, in step 2), after the backing layer is covered on the drug-containing adhesive layer, a slitting process, a punching process and a packaging process are sequentially performed to obtain the semi-finished fentanyl transdermal patch.
7. A method for reducing impurities in a fentanyl transdermal patch, characterized in that: include: The semi-finished fentanyl transdermal patch is subjected to annealing treatment to obtain the fentanyl transdermal patch.
8. The method according to claim 7, characterized in that The impurities include 1-(2-phenylethyl)-4-(N-phenylpropionamide)-piperidine-N-oxide.
9. The method according to claim 7 or 8, characterized in that: The annealing treatment is carried out at 70-100° C. for 2-5 hours; Optionally, the annealing treatment is performed at 70 to 90° C. for 2 to 5 hours; Optionally, the annealing treatment is performed at 75 to 85° C. for 2 to 4 hours; Optionally, the annealing treatment is performed at 75 to 85° C. for 3 to 4 hours; Optionally, the annealing treatment is performed at 80° C. for 2 to 4 hours; Optionally, the annealing treatment is performed at 80° C. for 3 to 4 hours.
10. The method according to claim 9, characterized in that The semi-finished fentanyl transdermal patch is obtained by the following steps: 1) coating a raw material mixture containing fentanyl or a pharmaceutically acceptable salt thereof on a release layer to obtain a drug-containing adhesive layer, wherein the release layer and the drug-containing adhesive layer are in contact; 2) covering the drug-containing adhesive layer with a backing layer to obtain the semi-finished fentanyl transdermal patch; Optionally, in step 2), before covering the backing layer on the drug-containing adhesive layer, the drug-containing adhesive layer is dried in advance; Optionally, in step 2), after the backing layer is covered on the drug-containing adhesive layer, a slitting process, a punching process and a packaging process are sequentially performed to obtain the semi-finished fentanyl transdermal patch.